Sleep Apnea Syndrome in Patients with Chronic Cerebral Venous Insufficiency on the Background of Chronic Obstructive Pulmonary Disease (Global Journal of Medical Research, 2019)
A clinical instrumental examination and polysomnographic examination were performed in 94 patients with chronic cerebral ischemia against the background of cerebral venous dysfunction with concomitant pathology -chronic obstructive pulmonary disease. 21 (22.3%) patients from the survey had clinical manifestations of obstructive sleep apnea/hypopnea sleep: mild -3, moderate -11, severe -7. A significant correlation was shown between body mass index, the number of apnea episodes and the level of hemoglobin saturation with oxygen, symptoms of cerebral venous dysfunction. No correlation was found between forced expiratory volume indicator and for the 1 st second. It should be assumed that in the pathogenesis of obstructive sleep apnea/hypopnea syndrome in chronic obstructive pulmonary disease, the degree of obesity and cerebralvenous dysfunction are more important, and not the severity of obstruction of the lower respiratory tract.
Keywords: obstructive sleep apnea/hypopnea syndrome; polysomnography; cerebral venous dysfunction